Exploitation and Exploration Climates' Influence on Performance and Creativity: Diminishing Returns as Function of Self-Efficacy. (March 2018) - Hirst, Giles; van Knippenberg, Daan; Zhou, Qin; Zhu, Cherrie Jiuhua; Tsai, Philip Cheng-Fei
In response to calls for multilevel research examining individual and meso-level processes to understand how exploitation and exploration dynamics play out in teams, we propose that individual in-role performance (cf. exploitation) and creativity (cf. exploration) are associated with team exploitation and exploration climate respectively, and this influence is moderated by domain specific performance and creative self-efficacy respectively. Studying 317 engineers in 70 teams across three national regions, we theorize and find domain-specific evidence that when individual self-efficacy is high, team climate has diminishing performance (exploitation climate × performance self-efficacy) and creative (exploration climate × creative self-efficacy) benefits. By simultaneously studying creativity and performance, our study helps understand the differences and communalities in the drivers of those outcomes in identifying both the domain-specific character of these influences and the similarity in how these influences play out.